Efficacy of antiresorptive agents bisphosphonates and denosumab in mitigating hypercalcemia and bone loss in primary hyperparathyroidism: A systematic review and meta-analysis - Rajput, Swati; Dutta, Aditya; Rajender, Singh; Mithal, Ambrish; Chattopadhyay, Naibedya (Frontiers in Endocrinology, 2023)
Abstract Purpose: Primary hyperparathyroidism (PHPT) is characterized by increased bone remodeling and hypercalcemia. Parathyroidectomy (PTX), the current standard of care, is recommended in all symptomatic and some groups of asymptomatic patients. Anti-resorptive treatments (bisphosphonates and denosumab) have been used in patients where PTX is refused or contraindicated. In this meta-analysis, we investigated the effectiveness of anti-resorptives in preventing/treating PHPT-induced bone loss and mitigating hypercalcemia. Method: PubMed, Scopus, and Cochrane Library databases were searched for articles with keywords containing PHPT, bisphosphonates, and denosumab in various combinations. We extracted and tabulated areal BMD (aBMD), serum mineral, and bone turnover parameters from the qualified studies and used comprehensive meta-analysis software for analysis. Results: Of the 1,914 articles screened, 13 were eligible for meta-analysis. In the pooled analysis, 12 months of anti-resorptive (bisphosphonates and Denosumab) treatments increased aBMD at the lumbar spine (SDM=0.447, 95% CI=0.230 to 0.664, p=0.0001), femoral neck (SDM=0.270, 95% CI=0.049 to 0.491, p=0.017) and increased serum PTH (SDM=0.489, 95% CI=0.139 to 0.839, p=0.006), and decreased serum calcium (SDM=-0.545, 95% CI= -0.937 to -0.154, p=0.006) compared with baseline. 12 months of bisphosphonate treatment significantly increases aBMD only at the lumbar spine (SDM=0.330, 95% CI=0.088 to 0.571, p=0.007) with a significant increase in serum PTH levels (SDM=0.546, 95% CI= 0.162 to 0.930, p=0.005), and decrease in serum calcium (SDM= -0.608, 95% CI=-1.048 to -0.169, p=0.007) and bone-turnover markers (BTMs) compared with baseline. Denosumab treatment for 12 months significantly increases aBMD at both the lumbar spine (SDM=0.828, 95% CI=0.378 to 1.278, p=0.0001) and femur neck (SDM=0.575, 95% CI=0.135 to 1.015, p=0.010) compared with baseline. Mean lumbar spine aBMD (SDM=0.350, 95% CI=0.041 to 0.659, p=0.027) and serum PTH (SDM=0.602, 95% CI= 0.145 to 1.059, p=0.010) were significantly increased after 12 months of alendronate treatment compared with placebo. When compared with baseline, alendronate significantly decreases BTMs after 12 months and increases aBMD without altering the PTH and calcium levels after 24 months. Conclusion: Anti-resorptives are effective in mitigating bone loss and hypercalcemia in PHPT while maintaining or increasing aBMD. PTX reversed all changes in PHPT and normalized PTH levels.